Recent advances of anti-tumor nano-strategies via overturning pH gradient: alkalization and acidification - Qiufang Gong; Xuejiao Song; Yao Tong; Lixuan Huo; Xuefen Zhao; Yingying Han; Wei Shen; Jiaxi Ru; Xian Shen; Chao Liang (Journal of Nanobiotechnology)
Abstract The acidic tumor microenvironment, a hallmark of many solid tumors, is primarily induced by the high glycolytic rate of tumor cells. To avoid acidosis, tumor cells ingeniously maintain an acidic extracellular pH while keeping a relatively alkaline intracellular pH. Overturning the unique pH gradient of tumor cells has exhibited to be a viable approach for cancer therapy. In this review, the formation and regulatory mechanisms of the acidic microenvironment in solid tumors will be firstly outlined. Subsequently, we will comprehensively summarize the latest advancements in anti-tumor therapy via using nanomedicines to manipulate the tumor pH gradient, including acidifying intracellular environment and alkalizing extracellular environment. Following this, we will discuss the future potential of strategies employing nanomedicines to reverse tumor pH gradient. This review aims to foster research on therapeutic approaches targeting the pH regulation of solid tumors and holds an optimistic outlook for the future development of this field.